Violence against women in the Muslim communities - Kamaruddin, Zaleha (s.n, 2012)
This paper presents an analysis of the patterns of violence directed toward Muslim women and the underlying mechanisms that permit the emergence and perpetuation of these patterns in some Muslim communities. This paper hosts discussions and analyses based on data collected through survey and non-interventional methods such as library and online research. It begins with defining the problem in focusing on violence against women in three major categories of interest: i.e. physical abuse, psychological abuse and deprivation of resources for physical and psychological well being. It is then followed by a survey of violence against women in selected Muslim communities. The third part presents an analysis from the Islamic perspective. This analysis would assist in formulating a strategic framework, which is Shariah compliant as proposed in the final part of this paper. It is hoped that this framework would have key effects on social planning, and effective implementation of social policy for protection of Muslim women against violence.